Compact Measurement of the Optical Power in High-Power LED Using a Light-Absorbent Thermal Sensor: A Recent Study - Kim, Youyoung; Joo, Jae-Young; Kim, Jong-Min; Lee, Sun-Kyu (Newest Updates in Physical Science Research Vol. 6, 2021)
LED (Light-Emitting Diode) presents advantages such as luminescence, reliability, durability compared with conventional lighting. It has been widely applied for life, healthcare, smart farm, industry, and lighting from indoor to the automotive headlamp. However, the LED is vulnerable to thermal damage originated from the high junction temperature, especially in high power applications. Hence, it requires precise qualification on the optical power and the junction temperature from the pilot line to secure reliability. In this study, the photo-thermal sensor is proposed by employing a sheet-type thermocouple composed of photo-absorbent metal film and thermocouple. This sensor aims low-cost qualification in pilot line for high-power luminous devices and optical monitoring of costly luminaire such as automobile LED headlamp. The sensor is designed to detect the increased temperature response of LED hot spots from the transferred thermal power and absorbed optical power. The temperature response of each sheet-type thermocouple is utilized as a signal output of the absorbed optical power and hot spot temperature based on the introduced sensor equation. The modeling of the sensor equation is established based on the lumped capacitance model of each sheet-type thermocouples with consideration of the view factor and additional optical power absorption term. The proposed thermal sensor is evaluated by comparing the experiment with the measured reference value from the integrating sphere and the attached thermocouple at a junction. The experiment result reveals 3% of the maximum error for the optical power of 645 mW.